OP0035 Tolerance of Rituximab, Abatacept and Tocilizumab in Common Practice: Analysis of the 3 Registries of the French Society of Rheumatology (Air, Ora and Regate). (9th June 2015) - Gottenberg, J.-E.; Morel, J.; Ravaud, P.; Bardin, T.; Cacoub, P.; Cantagrel, A.; Combe, B.; Constantin, A.; Dougados, M.; Flipo, R.M.; Godeau, B.; Hachulla, E.; et al.
Abstract : Objectives: To perform a joint analysis of the safety of abatacept (ABA), rituximab (RTX) and tocilizumab (TCZ) in real life. Methods: The AIR, ORA and REGATE French Society of Rheumatology registries follow up prospectively patients with rheumatoid arthritis treated with RTX, ABA or TCZ. The analyses took into account serious infections that occurred in the 12 months that followed an infusion of rituximab in the absence of initiation of a new biologic or those who occurred under abatacept or tocilizumab or in the 3 months that followed their discontinuation, in the absence of initiation of a new biologic. Serious infections and cancers were validated by the review of the charts of patients. Results: 1980 patients treated with RTX (current follow up of 6844 patient-years), 1024 patients with ABA (2882 patient-years), and 1503 patients with TCZ (1552 patient-years) (database of January 2013 for RTX and ABA and August 2013 for TCZ). – Serious infections: 309 serious infections occurred under RTX (4.5 serious infections/100 patient/years). 102 serious infections occurred under ABA (3.5 serious infections/100 patient/years). 55 serious infections occurred under TCZ (5.2 serious infections/100 patient/years). 3 tuberculosis infections (0.04/100 patient/years) occurred under RTX, 2 (0.07/100 patient/years) under ABA and no tuberculosis under TCZ. – Cancers: 85 cancers occurred under RTX (1.2/100 patient-years) including 14 non-melanoma skin cancers (0.2/100 patient/years), 71 solid cancers and haematological malignancies (1.0/100 patient/years) including 8 haematological malignancies (0.1/100/patient/years with 1 lymphoma).40 cancers occurred under ABA (1.4/100 patient/years) including 13 non-melanoma skin cancers (0.5/100 patient/years), 27 solid cancers and hematological malignancies (0.9/100 patients/year) including 4 haematological malignancies (0.14/100 patient/years, without lymphoma). 10 cancers were observed under TCZ (1.0/100 patient/years) including 2 non melanoma skin cancers (0.19/100/patient/years) 8 solid cancers and haematological malignancies 0.8/100 patient/years) including 3 haematological malignancies (0.29/100 patient/years) with 3 lymphomas. Conclusions: Incidences of serious adverse events in real life patients with comorbidities were similar under ABA, RTX and TCZ to what is expected in rheumatoid arthritis treated with anti-TNF. With ABA, RTX and TCZ, the incidence of tuberculosis is low. Adjusted statistical comparisons of safety, efficacy and drug retention rate of these 3 biologics are currently performed. Disclosure of Interest: None declared